Bacterial Communities Involved in Soil Formation and Plant Establishment Triggered by Pyrite Bioweathering on Arctic Moraines - F. Mapelli; R. Marasco; A. Rizzi; F. Baldi; S. Ventura; D. Daffonchio; S. Borin (Microbial Ecology, 2011)
In arctic glacier moraines bioweathering primed by microbial iron oxidizers creates fertility gradients that accelerate soil development and plant establishment. With the aim of investigating the change of bacterial diversity in a pyrite weathered gradient, we analyzed the composition of the bacterial communities involved in the process by sequencing 16S rRNA gene libraries from different biological soil crusts (BSC). Bacterial communities in three BSC of different morphology, located within one meter distance downstream a pyritic conglomerate rock, were significantly diverse. The glacier moraine surrounding the weathered site showed wide phylogenetic diversity and high evenness with 15 represented bacterial classes, dominated by Alphaproteobacteria and pioneer Cyanobacteria colonizers. The bioweathered area showed the lowest diversity indexes and only 9 bacterial families, largely dominated by Acidobacteriaceae and Acetobacteraceae typical of acidic environments, in accordance with the low pH of the BSC. In the weathered BSC iron oxidizing bacteria were cultivated, with counts decreasing along with the increase of distance from the rock, and nutrient release from the rock was revealed by ESEM-EDX analyses. The vegetated area showed the presence of Actinomycetales, Verrucomicrobiales, Gemmatimonadales, Burkholderiales and Rhizobiales, denoting a bacterial community typical of developed soils and indicating that the lithoid substrate of the bare moraine was here subjected to an accelerated colonization, driven by iron oxidizing activity.